Konflik Pekerjaaan Keluarga Futuristik dan Nurturistik: Dimensi Baru dalam Konflik Pekerjaaan Keluarga - Sih Darmi Astuti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2018)
Currently there are two of the three men who work have a wife who works, so families with dual career couples have become a norm. In Indonesia, more and more women are working outside their home, with their main reason (59%) is to increase income. This condition raises the pressure of work and family roles are incompatible with each other, known as Work-Family Conflict. The study concerning the topic initially utilized unidimensional scale measurements, but recently a lot of studies have employed multidimensional scale measurements.. Research gaps are also found in several studies with different results. This study offers the development of the multidimensional scale measurement of two dimensions, namely: futuristic and nurturistik in the measurement of work-family conflict, by combining role theory, social exchange theory and conservation of resources theory.